2014
DOI: 10.4028/www.scientific.net/amm.672-674.154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrothermal Pretreatment on the Content and Structure of Lignin Extracted from Corncob

Abstract: A systematic hydrothermal pretreatment of corncob has been conducted with an aim to trace the content and property of lignin during the pretreatment process. The result showed that the lowest content of lignin was obtained under the following condition: water-solid ratio is 3:1,180 °C for 90min with 0.4g auxiliary medium. TG and FTIR analysis has been conducted to investigate the thermal stability and structure of lignin, and the result indicated that hydrothermal pretreatment influenced the thermal stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These results suggest that the lignin reactivity and reaction behavior are significantly influenced by autohydrolysis pretreatment severity as well as the nature of the matrix that lignin is present in. Gao et al reported that hydrothermal pretreatment also influenced the thermal stability and structure of lignin in corncob [98].…”
Section: Hot Water Pretreatmentmentioning
confidence: 98%
“…These results suggest that the lignin reactivity and reaction behavior are significantly influenced by autohydrolysis pretreatment severity as well as the nature of the matrix that lignin is present in. Gao et al reported that hydrothermal pretreatment also influenced the thermal stability and structure of lignin in corncob [98].…”
Section: Hot Water Pretreatmentmentioning
confidence: 98%
“…14 The carbon source required for the microorganism at the later stage of the reaction must be obtained by decomposing insoluble cellulose. But because of the inuence of lattice structure, and the cross-linking effect of cellulose, hemicellulose and lignin, which is not conducive to the decomposition of carbon source, 15 of the carbon supply is inappropriate in the later. Therefore, SRB metabolic rate decreased, and it is not conducive to treatment of AMD.…”
Section: Introductionmentioning
confidence: 99%